Impedâncio-phmetria esofágica e resposta ao inibidor de bomba de prótons na doença do refluxo faringolaríngeo com disfonia crônica - Matos, Anna Caroline Rodrigues de Souza (2020)
The larygopharyngeal reflux disease (LPRD) is an inflammatory condition of the upper aerodigestive tract due to the direct or indirect effects of reflux of gastroduodenal content in the larynx and pharynx. It has great importance in otorhinolaryngological clinical practice and occurs in 4 to 30% patients who are treated by this specialty and, among those with complaints of dysphonia, this prevalence can reach 55%. The diagnosis of LPRD remains a challenge. The aim of this study was to evaluate the multichannel intraluminal impedance pH-monitoring (MII-pH) in patients with chronic dysphonia and LPRD related to the response to treatment proton pump inhibitor (PPI). A group of 21 patients was assessed using Reflux symptom index (RSI) and Reflux finding score (RFS) before and after treatment with PPI (pantoprazole 40mg, twice daily) for 8 weeks. They performed MII-pH prior to treatment as well as upper disgestive endoscopy. Patients who had a drop in RSI or RFS greater than or equal to 50% responded to treatment. The clinical and laryngoscopic characteristics found were compatible with the literature and a greater number of patients responded clinically to the treatment when compared to the laryngoscopic response. Most patients had na acid exposure time (AET) within the normal range and a positive correlation was observed between AET and the total number of distal and proximal reflux and a negative correlation between AET and Mean nocturnal baseline impedance (MNBI). Evaluating the response to treatment in relation to the imp-Ph parameters performed before it started, it was observed that patients who responded clinically had less acid exposure in orthostasis and greater distal MNBI. Those who obtained laryngoscopic improvement, on the other hand, had a higher number of non-acid distal refluxes. However, none of these parameters was able to predict the response to treatment with PPI. Thus, it is concluded that the AET is consistent in the MII-pH performed. However, it was not possible to identify predictive factors for response to PPI treatment at MII-pH. Further studies are needed with a larger number of patients, control group and placebo.